Agro-ecology as an alternative food security for indigenous communities - Sámano Rentería, Miguel Angel (Revista Mexicana de Ciencias Agrícolas, 2018)
The world economy is facing a global financial crisis; the capital accumulation model shows signs of exhaustion. This has resulted in the increase in food prices between April, 2007 and April, 2008; international food prices rose 54% in the main cereals (92%) and oil (84%). (FAO, FAOSTAT, index of food prices, Gómez, 2008) and the number of poor people has increased to such an extent that in 2010 it is considered that in the world, one billion people are hungry. FAO estimated that, the number of undernourished people in 2008 could have reached 915 million and will exceed 1000 million in 2009. (Un Millennium Goals Report 2010). The right to have food is a fundamental human right, and should seek alternatives to eliminate the scourge of hunger.
Keywords: Agro-ecology; food security; indigenous communities